Analisis Penurunan Pada Kinerja Perangkat Desa di Desa Kiara Sari - Nenden Fitria Nuraeni; Cecep Hermana (Universitas Batanghari, 2022)
This study aims to clearly identify, interpret and analyze how the work environment and work performance affect the performance of village officials in the Kiarasari Village office, Compreng District. Researchers used descriptive qualitative research methods, when this research was carried out from February 2022 to August 2022. The sources of data obtained were primary data from interviews and secondary data sources from data analysis from villages and sources such as books, journals, and documents. support, while the data collection techniques by means of interviews, observation, and documentation, while for the validity test using the credibility test, transferbility test, dependability test, and conformity test. Based on the results of the research analysis, it can be concluded that the decline in the performance of the Kiarasari Village apparatus is caused by several factors and many things, the data from the interviews and as well as the filling of the instrument shows that there are several factors that cause a decrease in the performance of the village apparatus, including: reduced responsibility and authority, effectiveness and efficiency, initiative and discipline, triggered by working conditions that do not provide facilities, as well as work comfort for village officials.